Study of Active Learning Processes in Integrated Thematic Learning in Class IV - Handari, Susi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research aims to investigate the implementation of the active learning process in integrated thematic learning in class IV of SDN No. 112/I Muara Bulian National Housing Complex. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that integrated thematic learning is student-centered, with an approach that allows students to experience integrated teaching from various subjects. The active learning process really encourages student participation, with observing activities as one of the main aspects that allows students to interact directly with learning content. Observations show that students responded positively to this learning approach, demonstrating high levels of engagement and the ability to think critically. The implication of this research is that the implementation of an active learning process in integrated thematic learning makes a significant contribution in improving the quality of learning and preparing students to face future challenges. These findings provide new contributions in the context of developing more dynamic and effective learning methods at the elementary level.